Ventricular tachycardia as the first manifestation of Churg-Strauss syndrome - Budanova, Margarita (J Cardiol Cases, 2016)
Life-threatening arrhythmias are often found in heart diseases, but they are rare as clinical symptoms of Churg-Strauss syndrome. We report a case of a 66-year-old woman with symptomatic monomorphic ventricular tachycardia as the first sign of Churg-Strauss syndrome. Cardiac manifestations were the main clinical symptoms of the disease, and changes in other organs were weakly expressed. Furthermore, increased serum IgG4 level was revealed. It was the reason for the differential diagnosis with IgG4-related diseases. Echocardiography, cardiac magnetic resonance imaging, and histopathological analysis of biopsies had an important role in diagnosis. <Learning objective: Ventricular arrhythmias are rare clinical symptoms of Churg-Strauss syndrome. This case is interesting because cardiac manifestations were the main clinical symptom of the disease, and changes in other organs were weakly expressed. Echocardiography, cardiac magnetic resonance imaging, and histopathological analysis of biopsies had an important role in diagnosis. Increased serum IgG4 level was the reason for the differential diagnosis with IgG4-related diseases. Churg-Strauss syndrome should be considered as part of the differential diagnosis in patients with noncoronary ventricular arrhythmias.>